Significance of functional hepatic resection rate calculated using 3D CT/(99m)Tc-galactosyl human serum albumin single-photon emission computed tomography fusion imaging - Tsuruga, Yosuke (World J Gastroenterol, 2016)
AIM: To evaluate the usefulness of the functional hepatic resection rate (FHRR) calculated using 3D computed tomography (CT)/(99m)Tc-galactosyl-human serum albumin (GSA) single-photon emission computed tomography (SPECT) fusion imaging for surgical decision making. METHODS: We enrolled 57 patients who underwent bi- or trisectionectomy at our institution between October 2013 and March 2015. Of these, 26 patients presented with hepatocellular carcinoma, 12 with hilar cholangiocarcinoma, six with intrahepatic cholangiocarcinoma, four with liver metastasis, and nine with other diseases. All patients preoperatively underwent three-phase dynamic multidetector CT and (99m)Tc-GSA scintigraphy. We compared the parenchymal hepatic resection rate (PHRR) with the FHRR, which was defined as the resection volume counts per total liver volume counts on 3D CT/(99m)Tc-GSA SPECT fusion images. RESULTS: In total, 50 patients underwent bisectionectomy and seven underwent trisectionectomy. Biliary reconstruction was performed in 15 patients, including hepatopancreatoduodenectomy in two. FHRR and PHRR were 38.6 ± 19.9 and 44.5 ± 16.0, respectively; FHRR was strongly correlated with PHRR. The regression coefficient for FHRR on PHRR was 1.16 (P < 0.0001). The ratio of FHRR to PHRR for patients with preoperative therapies (transcatheter arterial chemoembolization, radiation, radiofrequency ablation, etc.), large tumors with a volume of > 1000 mL, and/or macroscopic vascular invasion was significantly smaller than that for patients without these factors (0.73 ± 0.19 vs 0.82 ± 0.18, P < 0.05). Postoperative hyperbilirubinemia was observed in six patients. Major morbidities (Clavien-Dindo grade ≥ 3) occurred in 17 patients (29.8%). There was no case of surgery-related death. CONCLUSION: Our results suggest that FHRR is an important deciding factor for major hepatectomy, because FHRR and PHRR may be discrepant owing to insufficient hepatic inflow and congestion in patients with preoperative therapies, macroscopic vascular invasion, and/or a tumor volume of > 1000 mL.